Bacterial GtfB Augments Candida albicans Accumulation in Cross-Kingdom Biofilms. (September 2017) - Ellepola, K.; Liu, Y.; Cao, T.; Koo, H.; Seneviratne, C.J.
Streptococcus mutans is a biofilm-forming oral pathogen commonly associated with dental caries. Clinical studies have shown that S. mutans is often detected with Candida albicans in early childhood caries. Although the C. albicans presence has been shown to enhance bacterial accumulation in biofilms, the influence of S. mutans on fungal biology in this mixed-species relationship remains largely uncharacterized. Therefore, we aimed to investigate how the presence of S. mutans influences C. albicans biofilm development and coexistence. Using a newly established haploid biofilm model of C. albicans, we found that S. mutans augmented haploid C. albicans accumulation in mixed-species biofilms. Similarly, diploid C. albicans also showed enhanced biofilm formation in the presence of S. mutans . Surprisingly, the presence of S. mutans restored the biofilm-forming ability of C. albicans bcr1Δ mutant and bcr1Δ/Δ mutant, which is known to be severely defective in biofilm formation when grown as single species. Moreover, C. albicans hyphal growth factor HWP1 as well as ALS1 and ALS3, which are also involved in fungal biofilm formation, were upregulated in the presence of S. mutans . Subsequently, we found that S. mutans –derived glucosyltransferase B (GtfB) itself can promote C. albicans biofilm development. Interestingly, GtfB was able to increase the expression of HWP1, ALS1, and ALS3 genes in the C. albicans diploid wild-type SC5314 and bcr1Δ/Δ, leading to enhanced fungal biofilms. Hence, the present study demonstrates that a bacterial exoenzyme (GtfB) augments the C. albicans counterpart in mixed-species biofilms through a BCR1 -independent mechanism. This novel finding may explain the mutualistic role of S. mutans and C. albicans in cariogenic biofilms.